Mammalian Diversity of Degraded Forest Habitats around Assam University Campus, Cachar, Assam, India, with Notes on Conservation Status - Mazumdar, K.; Soud, R.; Gupta, A. (Our Nature, 2012)
Barak valley in South Assam remains poorly investigated in terms of faunal diversity, especially mammals. This paper inventories 19 species of mammals belonging to 14 families in the degraded forests of Assam University Campus, Silchar, Assam and those maintained by the tea gardens of this area. Of these, three are in the IUCN endangered (EN) and two in vulnerable (VU) categories. The threats faced and conservation priorities are also discussed. DOI: http://dx.doi.org/10.3126/on.v9i1.5742